2019
DOI: 10.1039/c8md00555a
|View full text |Cite
|
Sign up to set email alerts
|

Interrupting cyclic dinucleotide-cGAS–STING axis with small molecules

Abstract: The cyclic dinucleotide-cGAS–STING axis plays important roles in host immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 126 publications
0
15
0
Order By: Relevance
“…Moreover, acute tissue damage, as seen in the context of myocardial infarction, has been shown to involve cGAS-STING activation with adverse outcomes 203 . Based on these considerations, efforts are being undertaken to develop compounds that antagonize the cGAS-STING signalling cascade at various levels: DNA binding of cGAS, catalytic activity of cGAS, cGAMP binding to STING and the use of allosteric modulators of STING, such as inhibitors of palmitoylation 204 . Cyclic GMP-AMP synthase (cGAS) consists of a two-lobed catalytic domain and an extended amino-terminal (N-terminal) domain.…”
Section: Box 2 -Cgas-sting Signalling In Disease and Therapymentioning
confidence: 99%
“…Moreover, acute tissue damage, as seen in the context of myocardial infarction, has been shown to involve cGAS-STING activation with adverse outcomes 203 . Based on these considerations, efforts are being undertaken to develop compounds that antagonize the cGAS-STING signalling cascade at various levels: DNA binding of cGAS, catalytic activity of cGAS, cGAMP binding to STING and the use of allosteric modulators of STING, such as inhibitors of palmitoylation 204 . Cyclic GMP-AMP synthase (cGAS) consists of a two-lobed catalytic domain and an extended amino-terminal (N-terminal) domain.…”
Section: Box 2 -Cgas-sting Signalling In Disease and Therapymentioning
confidence: 99%
“…HSV-2 has evolved multiple strategies to counteract this pathway, inhibiting IFN β production and evading host immunity [ 21 ]. Mangostin is a STING-targeted pathway agonist [ 22 ]. The binding activity of all the three was superior to that of mangostin, with geraniin showing the strongest binding activity (−11.71 kcal/mol), as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies on STING agonists focus on the optimization of cyclic dinucleotide (CDN) analogs and the screening of novel small molecule agonists. [110][111][112][113] CDNs, effective STING activators, are second messengers common in the immune systems of prokaryotes and eukaryotes. [114][115][116] There are two sources of CDNs: the cGAS pathway, which produces the atypical dinucleotide 2ʹ,3ʹ-cGAMP after the detection of cytoplasmic DNA; the other is found in the cytoplasm owing to the presence of pathogens.…”
Section: Agonists Of Stingmentioning
confidence: 99%
“…[114][115][116] There are two sources of CDNs: the cGAS pathway, which produces the atypical dinucleotide 2ʹ,3ʹ-cGAMP after the detection of cytoplasmic DNA; the other is found in the cytoplasm owing to the presence of pathogens. 112,[117][118][119] Numerous studies found that CDNs have strong antitumor effects and application prospects in the treatment of melanoma, colon cancer, and oral cancer. 39,[120][121][122] However, there are limitations in the use of CDNs as candidate drugs.…”
Section: Agonists Of Stingmentioning
confidence: 99%